The ASEAN’s Limitation of Regional Digital Integration: How Digital Sovereignty Overlaps Regional Organization Effectiveness: English - Andrew Elnathan; Wishnu Mahendra Wiswayana (Journal of Social Research, 2025)
The rapid development of digital transformation has profoundly shaped economic and political interactions globally, with the “new oil of the 21st century.” Southeast Asia faces unique challenges in balancing national digital sovereignty and regional digital integration. This study critically examines ASEAN's effectiveness in fostering a regional digital integration amidst diverse data governance policies and digital sovereignty concerns across its member states. Through a qualitative literature review and focused case studies of Indonesia, Singapore, Vietnam, and the European Union, it reveals how diverse national interests, fragmented regulations, and infrastructural disparities obstruct ASEAN’s digital integration ambitions. While ASEAN presents frameworks such as the ASEAN Digital Economy Framework and the ASEAN Digital Masterplan 2025, implementation remains limited due to underlying sovereignty issues and ASEAN’s mandate of non-interference. Comparisons with the European Union’s centralized digital sovereignty and regulatory harmonization highlight ASEAN’s institutional and political constraints. The study contributes to the discourse on new regionalism by addressing the underexplored intersection of digital sovereignty and regionalism in Southeast Asia, offering insights into the complex dynamics shaping ASEAN Digital Regionalism and its prospects.